Perceptions of farmers about their motivation to manage agricultural risk in Malaysia - Ali, Muhammad; Man, Norsida; Muharam, Farrah Melissa (Pakistan Agricultural Research Council, 2019)
Climate change affects not only livelihood but also the motivation of farmers. Perceptions of farmers could be influenced by a risky environment to become either risk averse or risk neutral. Indeed, less attention has been paid by researchers to empirically examine the motivation of farmers to manage their agricultural risks exclusively from the lens of Malaysia. Thus, the research was formulated to assess the motivation of farming community towards agricultural risk management in Malaysia. The research data were gathered through pre designed interview schedule from 360 randomly selected farmers through multistage cluster sampling technique. In order to measure motivation of respondents, likert scale items comprising 1 as strongly disagree to 5 as strongly agree were used. The research findings reveal that farmers were motivated to manage their agricultural risks and overall their motivation level was high. Nevertheless, still efforts are required by all stakeholders to keep the motivation level high of farming community at local, regional and international level. Agricultural extension workers as change agents are required to keep the motivation level high otherwise, food security and bread and butter of farmers would become jeopardized by climate changes at the national and global level.